Assessment of Emergency Exit Pathways and Fire Safety Measures in Football Stadium X: An Examination Following Indonesian Guidelines - Maududi, Affan Al; Fanani, Erianto; Marji, Marji; Kustono, Djoko (citeus, 2024)
The most significant football stadium riot tragedy occurred at the National Stadium (Estadio Nacional) in Lima, Peru, resulting in 362 fatalities. The second largest tragedy transpired at the Kanjuruhan Stadium, Malang Regency, Indonesia, leading to 135 deaths. This research aims to evaluate the conformity of evacuation routes and fire protection systems at the one of Football Stadium in Greater Malang, in accordance with the standards and regulations applicable in Indonesia. This analytical descriptive study employs a quantitative research design. The research process involved examining the factual conditions on the ground and subsequently comparing the suitability of evacuation routes and fire protection systems against the standard benchmarks and regulations in place in Indonesia. The results of this study indicate that the conformity level of the evacuation routes, comprising emergency stairs, evacuation routes, safety signs, assembly points, and emergency exits, is at 61.9 percent, denoting adequate compliance. Conversely, the active fire protection systems, encompassing portable fire extinguishers (APAR), hydrants, fire alarms, fire detectors, and sprinklers, show 0 percent compliance, meaning no conformity exists. This study is anticipated to serve as a reference for enhancing evacuation routes and fire protection systems at Football Stadium X: stadium in Greater Malang.